Translations of the Psalms in Old Polish Biblical-Apocryphal Narrative Texts: The Beginnings of Vernacular Religious Language. Issue 1 (April 2023) - Rojszczak-Robińska, Dorota
The Old Polish New Testament apocrypha are the most extensive written records of a Polish medieval religious language. The aim of this article is to analyze ways in which excerpts from the Psalms operate in these texts. No full Polish medieval translation of the Bible has been preserved, so it is the apocrypha that shape our understanding of the folk Bible in medieval Poland. Medieval authors came up with different translation strategies: formal and dynamic equivalence, as well as paraphrase and summary. The authors used the Latin text freely, adapting it to the subject, removing inconvenient passages and adding others. However, fragments of psalms are almost always translated accurately, word for word, duly accounting for the Latin word order. The manner of translating psalms is different from the way Old Polish authors translated texts they knew as bilinguals.